INDUCTION BY ANTIBIOTICS AND COMPARATIVE SENSITIVITY OF L-PHASE VARIANTS OF STAPHYLOCOCCUS AUREUS - Molander, C. W. (1964)
Molander, C. W. (Cedars of Lebanon-Mount Sinai Hospitals, Los Angeles, Calif.), B. M. Kagan, H. J. Weinberger, E. M. Heimlich, and R. J. Busser. Induction by antibiotics and comparative sensitivity of L-phase variants of Staphylococcus aureus. J. Bacteriol. 88:591–594. 1964.—The penicillins, cephalothin, vancomycin, and bacitracin were found to be less inhibitory to the L-phase variants than to their respective parent bacteria. Those antibiotics not considered to be primarily inhibitors of cell-wall synthesis were, in general, somewhat more inhibitory to the L form than to their parent bacteria. Only the penicillins and cephalothin readily induced L-phase variation. Novobiocin induced pleomorphic growth resembling the earliest stages of L-phase transformation. Failure of observable induction by bacitracin and vancomycin suggests that these two antibiotics affect cell-wall synthesis in a manner different from the penicillins, or that L-phase transformation may require more than “penicillin-like” interference with cell-wall synthesis.